A novel cancer-associated lncRNA, LINC01123, participates in tumor progression, metabolism, immune escape, and resistance - Liu, Qiang; Huang, He; Zhang, Shuwen; Liu, Fangteng; Lou, Ting (Frontiers in Immunology, 2025)
Long Intergenic Non-Protein Coding RNA 1123 (LINC01123), located on human chromosome 2q13, is a pivotal factor in tumorigenesis, exerting multifaceted oncogenic effects. Its expression strongly correlates with clinicopathological features, patient survival, and disease progression. In vivo and in vitro experiments further demonstrate that LINC01123 influences diverse cellular processes, including proliferation, apoptosis, viability, migration, invasion, stemness, and tumor growth. Notably, it also regulates metabolic reprogramming, immune escape, and tumor cell resistance to treatment. LINC01123 is regulated by multiple transcription factors and participates in gene regulation through protein interactions and competitive endogenous RNA (ceRNA) networks, thereby modulating cancer-promoting effects. This work systematically elucidates its primary functions and molecular mechanisms driving cancer initiation and progression, suggesting that LINC01123 might serve as a novel potential oncogenic driver and biomarker in various cancers.